State Income Disparity In Relation To National Development Plans In Malaysia - Veerasingam, Sivabalasingam (2007)

(untitled)
Malaysia envisaged of bringing the low-income states to the general income level by 1985 (First Malaysia Plan, 1965). However, after 49 years of independence and equivalent years of economic planning, the national agenda of bridging the income divide across states in Malaysia remains an unresolved issue. This study is designed to address the question why for the last four decades and with nine National Development Planning programmes should substantial state income disparities be of great concern to the public, politicians and the academic circle. In tandem with the general objective, we examined whether poor states in Malaysia are growing faster than rich states (-convergence). In consonance with our comparative and non-parametric results, we find no econometric evidence to support  -convergence in Malaysia. In addition, an examination on sigma convergence, namely the tendency for cross-sectional dispersion of real per capita income to decline over time suggests that the dispersion in income across states in Malaysia has in fact widened. Our results also indicate that the strategies in the Third Malaysia Plan were the most effective while the rest did not meet their intended target of reducing the income divide across states in Malaysia. We also find evidence to suggest that the rising income inequality is not a common phenomenon but mainly due to greater variation in real per capita income between Kelantan, Kedah, Perlis, Pahang and Sabah and the rest of the states in the country. A growth model based on the System Generalized Method of Moments technique suggest that investment has a positive impact, while agriculture sector and population growth rate has a negative impact on income growth. Given these findings, we conclude that despite 49 years of independence and equivalent years of economic planning, the national agenda of bridging the income divide between the low and high-income states, in particular between Kelantan, Kedah, Perlis, Pahang and Sabah and the more developed states in the country did not materialise. This failure is largely associated to the ineffectiveness of the national regional policy. To mitigate the income divide across states in the country, greater industrial and investment activities are humbly recommended.